Feasibility Analysis and Improvement of Comprehensive Meteorological Drought Index in Chongzuo - ZHANG Gang; TENG Jiduan; ZHANG Lijie; LI Yuntang; QIN Zhuanghao; LUO Lihua; HUANG Yongliang (Renmin Zhujiang)
For the “unreasonably worse drought” showed by the comprehensive meteorological drought index, this paper proposes a non-linear unequal weight calculation method and an improved comprehensive meteorological drought index (CI43), and analyzes the applicability of CI43 in drought monitoring and evaluation based on historical data at 12 metrological stations in Chongzuo from 1961 to 2015. The results showed that: ① The monitoring results by CI and CI43 are relatively close on the drought monitoring process. The improved CI43 avoids effectively the unreasonably worse drought showed by CI; ② The corrected drought grade standard of CI43 avoids the overestimating or underestimating the drought grade, so the evaluation results by CI43 are more scientific and reasonable; ③ The monitoring results by CI43 on the occurrence, development and relief of drought are more consistent with the actual drought. Therefore, we can concluded that the CI43 is more suitable for drought monitoring and evaluation in Chongzuo.